Communication Strategies and Intensive Interaction Therapy Meet the Theology of the Body: Bioethics in Dialogue with People with Profound Disabilities. Issue 2 (9th January 2014) - Matthews, Pia
Abstract : Academic bioethics does not appear to be interested in communication and its ethical concerns unless communication is to do with issues such as capacity, consent, truth telling and confidentiality. In contrast practitioners are interested in actually communicating with their patients and they are often particularly perplexed when it comes to people with profound disabilities where communication appears disrupted. Although some new and not so new communication strategies, and especially intensive interaction, are available, little has been written on either the ethical concerns these may present or the deeper concepts that underpin them. This article explores the practical applications of some of these communication strategies. By engaging these strategies with theology, and specifically Pope John Paul's Theology of the Body, this article identifies and addresses some significant ethical issues that may arise, notably the risk of dualism and of objectifying the human person. Moreover it provides communication strategies with a rationale that goes beyond practicalities to one based on respect for human dignity, justice and solidarity.